2007
DOI: 10.1002/adfm.200600575
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Polymer/Liquid Crystal Composite Diffractive Optics by Multiphoton Methods

Abstract: Direct‐write multiphoton photolithography is used to prepare electrically switchable diffraction gratings having spacings as small as 4 μm. Surface‐relief gratings are written into poly(methyl methacrylate) films using a sample‐scanning confocal microscope and are characterized by using contact‐mode atomic force microscopy. The resulting polymeric channels are filled with nematic liquid crystals (LCs) and sandwiched between indium tin oxide‐coated coverslips to obtain functional devices. These devices exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Nanoscale composite materials via supporting nanoparticles onto another matrix exhibit novel structure and distinguished performance in catalysis 1 2 3 4 5 , optics 6 7 , electronics 8 9 , and other applications 10 . The methods developed for the synthesis of nanoparticles onto the matrix mainly include precipitation 11 12 , sol-gel 13 14 , microwave-assisted synthesis 15 16 , phase transitions and hydrothermal process 17 .…”
mentioning
confidence: 99%
“…Nanoscale composite materials via supporting nanoparticles onto another matrix exhibit novel structure and distinguished performance in catalysis 1 2 3 4 5 , optics 6 7 , electronics 8 9 , and other applications 10 . The methods developed for the synthesis of nanoparticles onto the matrix mainly include precipitation 11 12 , sol-gel 13 14 , microwave-assisted synthesis 15 16 , phase transitions and hydrothermal process 17 .…”
mentioning
confidence: 99%
“…The earliest implementations of such optical elements employed a variety of conventional lithographic methods to pattern surface relief structures into standard negative photoresists before they were transformed into an active device by adding a layer of indexmatched liquid crystalline material. [30][31][32][33][34][35][36] For example, a previous study demonstrated a switchable DOE for use in textured surface inspection. [30] In this case, a He-Cd laser was used to Direct laser writing is demonstrated by two-photon polymerization of multielement diffractive optical components that can be switched on and off with an applied voltage.…”
Section: Doi: 101002/adom202102446mentioning
confidence: 99%
“…Beam steering is relevant in several sectors of photonics, including microscopy, [24] displays, [25] object detection, [26] and optical tele-and data communication. [27,28] The existing technology involves devices like MEMS mirrors [29][30] or, for instance, phase gratings, [31][32][33] and is based on electrical, [34] electromechanical [35] or acousto-optic [36] effects. Nonetheless, optically tunable photonic components have been demonstrated for structures made by GST (Ge3Sb2Te6) and VO2 but their very complex, subwavelength-scale structuration (phase array devices) [37][38][39][40][41][42][43] requires extremely precise nanofabrication.…”
Section: Introductionmentioning
confidence: 99%